Pengaruh Pencatatan Keuangan dan Penggunaan Fintech terhadap Kinerja Keuangan UMKM dengan Efikasi Diri sebagai Variabel Moderasi - Ni Made Indah Pratiwi; I Nyoman Gede Arya Diatmika (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the regional economy, yet they still face challenges in financial management, which impacts their financial performance. This study aims to analyze the influence of financial record-keeping and financial technology (fintech) on the financial performance of MSMEs, with self-efficacy as a moderating variable. Using a quantitative approach, a sample of 100 MSME owners in Tabanan Regency was selected through purposive sampling using the formula of multiplying all indicators by 5-10. Data were collected using a questionnaire via Google Forms and analyzed using Partial Least Square–Structural Equation Modeling (PLS-SEM) with the help of SmartPLS version 4.1.1.4. The results show that financial record-keeping and fintech have a positive and significant effect on the financial performance of MSMEs. Additionally, self-efficacy has been proven to strengthen the influence of financial record-keeping and fintech on the financial performance of MSMEs. These findings suggest that the practices of financial record-keeping and the use of fintech will have a more optimal impact when supported by a high level of self-efficacy among MSME owners. Theoretically, this study supports the Resource-Based View (RBV) and Theory of Planned Behavior (TPB) in explaining the role of internal resources and psychological factors in the financial performance of MSMEs.